2014
DOI: 10.1890/13-2171.1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced wind strengthens top‐down control of an insect herbivore

Abstract: Abstract. Global wind speeds have decreased 5-15% over the last 30 years and are expected to continue decreasing in the future. However, little is known about how wind affects species and their interactions within communities. I experimentally tested the effects of wind on predator-prey interactions using soybean aphids and predatory multicolored Asian ladybeetles. First, I examined the direct effect of wind on aphids in a greenhouse without predators under three treatments: no wind, wind (oscillating fan), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 41 publications
0
29
1
Order By: Relevance
“…Thus, P. brassicae caterpillars are exhibiting a phenotypically plastic response to the presence or absence of wind because of enhanced enemy‐free‐space (Stamp, ) on wind‐exposed plants. On plants exposed to wind, it is clearly more difficult for visually foraging predators, such as birds and predatory wasps, to locate their prey or to alight on the plant as was demonstrated in the study by Barton ().…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, P. brassicae caterpillars are exhibiting a phenotypically plastic response to the presence or absence of wind because of enhanced enemy‐free‐space (Stamp, ) on wind‐exposed plants. On plants exposed to wind, it is clearly more difficult for visually foraging predators, such as birds and predatory wasps, to locate their prey or to alight on the plant as was demonstrated in the study by Barton ().…”
Section: Discussionmentioning
confidence: 88%
“…Despite the potential importance of wind and other abiotic factors on higher trophic level interactions, studies of how wind exposure affects herbivore susceptibility to predation are scant. In combined laboratory and field studies, Barton () showed that the density of predators, such as ladybirds, was lower, and concomitant predation of aphids was impeded, in plants and plots exposed to wind. Ladybirds took longer to find aphids on plants exposed to wind, thereby providing the aphids with a form of temporal “enemy‐free space” (Gols et al., ; Stamp, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that wind speed is, in part, a function of the difference in air temperature between regions, if anthropogenic warming results in a decrease in this temperature gradient then declining wind speeds would follow. Broad scale declines in wind speed have been well documented for the continental United States (Barton, 2014;Kulkarni & Huang, 2014;Pryor et al, 2009). Decreases of upwards to 15% over the last three decades have been observed over wide geographic regions in North America and elsewhere in the world (McVicar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the well-documented sensitivity of top predators to landscape alteration (Purvis et al 2000;Martinson and Fagan 2014) but suggest that for grassland insect communities, the decline of top predators does not necessarily lead to predator-mediated effects on herbivore communities. However, recent studies have shown that the regulatory effect of top predators on insects can be context dependent as a function of seasonality (Gratton and Denno 2003), wind speed (Barton 2014), and especially temperature (Hoekman 2010;Shurin et al 2012;Barton and Ives 2014). In the current context of global change, caution is therefore required when predicting the relative importance of predatormediated processes versus plant-mediated processes, as it is likely to change as a function of the focal stressors.…”
Section: Discussionmentioning
confidence: 99%